IMPLEMENTATION OF INTEGRATED QUALITY MANAGEMENT IN DEVELOPING STUDENT COMPETENCIES - Suryono, Suryono; Patimah, Siti (INCARE, International Journal of Educational Resources, 2023)
One effective approach in developing student competence is through the implementation of integrated quality management. This approach involves various aspects, including developing relevant curricula, interactive and innovative learning, comprehensive assessment, and increasing teacher competence. In the context of SMP IT Cendikia Tulang Bawang, this study aims to investigate the implementation of Integrated Quality Management in developing the competence of students at SMP IT Cendikia Tulang Bawang. The research was conducted using a qualitative approach and involved participants from school staff, teachers, students, and parents. Data was collected through observation, interviews and document analysis. The results of the study show that the implementation of Integrated Quality Management has a positive influence on the development of students' competencies. Strong leadership from the school, participation and active commitment from teachers, and parental involvement are important factors in this implementation. However, there are a number of problems encountered, including technical constraints in the use of educational technology and barriers to parental involvement. Therefore, this research also provides strategies for optimizing the implementation of Integrated Quality Management, including increasing teacher training, using innovative educational technology, and increasing the active involvement of parents. By implementing these strategies, it is hoped that schools can achieve better results in the development of student competencies. This research contributes to the development of education at SMP IT Cendikia Tulang Bawang and can be a reference for other schools that wish to implement Integrated Quality Management for developing student competencies.